2010
DOI: 10.1152/ajpcell.00562.2009
|View full text |Cite
|
Sign up to set email alerts
|

Role of neural-cadherin in early osteoblastic differentiation of human bone marrow stromal cells cocultured with human umbilical vein endothelial cells

Abstract: Li H, Daculsi R, Grellier M, Bareille R, Bourget C, Amedee J. Role of neural-cadherin in early osteoblastic differentiation of human bone marrow stromal cells cocultured with human umbilical vein endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 51 publications
6
41
0
Order By: Relevance
“…The role of Cx43 in osteogenesis and bone formation has been demonstrated in vitro using 2-D culture models of different osteoblastic cell lines [18] and in vivo using experimental models in mice [36]. In vitro, the present authors' previous results provide evidence of the function of endothelial cell interactions via gap junctional communication for the development of bone-forming cells [18,21,37]. In these experiments, the cell coupling and the functionality of the gap junctions were evidenced using specific inhibitors to Cx43 or gap junctions.…”
Section: Introductionsupporting
confidence: 55%
“…The role of Cx43 in osteogenesis and bone formation has been demonstrated in vitro using 2-D culture models of different osteoblastic cell lines [18] and in vivo using experimental models in mice [36]. In vitro, the present authors' previous results provide evidence of the function of endothelial cell interactions via gap junctional communication for the development of bone-forming cells [18,21,37]. In these experiments, the cell coupling and the functionality of the gap junctions were evidenced using specific inhibitors to Cx43 or gap junctions.…”
Section: Introductionsupporting
confidence: 55%
“…Similarly, cocultures on the SSE surface also displayed positive ALP and Alizarin red staining, which was not seen when the ASCs were grown alone on the same surfaces. In the present study, the ASCs are considered the cells that have gone through osteogenic differentiation because, under normal culture conditions, HMVECs would not differentiate into the osteolineage cells, 8,11,20,21,25 and additionally, in our preliminary studies, we did not see any mineralization occurring when the HMVECs were grown alone on the FA surfaces (data not shown). Taken together, this would suggest that HMVECs stimulated both osteogenic differentiation of ASCs and the subsequent mineralization process, which may be mediated by both the released endothelial signals and/or the intimate interaction between these two kinds of cells.…”
Section: Discussionmentioning
confidence: 72%
“…8 Still unclear is the precise role of endothelial cells on osteoblastic differentiation, but emerging studies have demonstrated that coculture of endothelial cells and mesenchymal precursor/stem cells stimulated the expression of bone phenotypic markers and enhanced the osteogenesis of cocultured mesenchymal cells. [9][10][11] Recently, we reported that the ordered fluorapatite (OR-FA) surface when used as a potential implant coating, showed good biocompatibility with different cell lines, that is, dental pulp stem cells and osteoblast-like MG-63 cells and supported the long-term growth and differentiation of these cells. [12][13][14] This OR-FA surface stimulated, in vitro, the expression of a set of pro-osteogenic transcripts and bone mineralization phenotypic markers of ASCs, and consistently accelerated and enhanced in vivo mineralized tissue formation.…”
mentioning
confidence: 99%
“…This study also clearly demonstrated that endothelial cells enhance the osteogenic differentiation of MSCs, as shown by histochemical staining for alkaline phosphatase. Although the precise role of endothelial cells on osteoblastic differentiation is still unclear, several studies have demonstrated a stimulatory effect of endothelial cells on alkaline phosphatase activity when in direct contact 2D co-cultures (Villars et al, 2000;Kaigler et al, 2005;Guillotin et al, 2008;Grellier et al, 2009a;Hager et al, 2009;Li et al, 2010). Grellier et al showed that endothelial cells supported osteogenesis of human osteoprogenitor cells, when co-immobilised within alginate micropspheres (Grellier et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%